Corporate Governance Quality, Board Gender Diversity and Corporate Dividend Policy: Evidence from Jordan - Ayat S. Al-Rahahleh (Australasian Accounting, Business and Finance Journal, 2017)
This paper examines the impact of corporate governance quality and board gender diversity on the corporate dividend policy for a set of all non-financial companies listed on Amman Stock Exchange (ASE) during the period 2009-2015. The results documented that corporate governance quality and board gender diversity proxies have positive impact on corporate dividend policy. The results also showed that the women representation on the boards of non-financial companies in Jordan is considered low relative to other countries. Particularly, the causes of the poor board gender diversity in Jordan range from lack of awareness about the benefits of gender diversity to the lack of legislation that regulates this issue. It is recommended to non-financial companies in Jordan to boost their compliance with the corporate governance code and adopt diversity policies to enhance the effectiveness of the boards and keep favorable relationships with their shareholders. Furthermore, regulatory bodies in Jordan should take a step towards encouraging gender diversity on boards.
Keywords: Corporate Governance Quality; Board Gender Diversity; Women on Boards; Female Directors; Corporate Dividend Policy